(3TQM fSHI GdeJabGJ hGdeNJdaGJ aj GdaQGFVs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO hGdJUdjI (B: (3CeG HYO aEf GdTGQM GdaGVd TeS GdOjf GHf GdafGQj bGd aj TQMg cJGH GdaQGjV aj HGH eYQaI GdaQhV fhYGf CMOgeG fSHI GdeJabGJ Edi BNQgs
(3BNQgG (B:s
(3hGdCQHYI SOS CQYI hYTQjf hGdKdGKI KefgG ceG eQ ajchf GdSOS eKd GdKef hKdKg gPG TQM GdTcd GdPj UhQg GdTGQN dHjGf GdfSH GdfabGJ hGdeNJdaGJ ef fhYj GdaQhV hGdMeO ddg Ydi GdJeGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdaQGFVs